Korelasi Ekspor Dan Impor Terhadap Neraca Perdagangan Dan Neraca Pembayaran Di Indonesia Tahun 2007-2016 - Wiryanti, Tutik (JURNAL BISNIS & AKUNTANSI UNSURYA, 2017)
The total export consist of gas and petroleum and non gas and petroleum to many countries. The total import consist of petroleum, mineral, agriculture, industry from many countries. The trade balance of Indonesia are notes of the total export minus the total import. Whereas the Indonesian balance of payment are notes of foreign transactions which to became revenue or payment from another countries. The aim of the research is to know of correlations and influence between the total export and import to the Indonesian balance of payment and the trade balance in 2007 - 2016. The research methods used library research from annual report of the Bank Indonesia since 2007 until 2016, BI and BPS website, other reference and then statistic analysis. The result of the research show that: (1) the total export and import were the linear and strong positive correlations relationship (R=1,00) to the trade balance,but Its were linear and the enough correlation relationship (R=0,631) to the Indonesion balance of payment in 2007 - 2016. (2) The total export and import were not an influence to the trade balance and Indonesian balance of payment in 2007 – 2016. Keywords : Export, Import, Trade Balance and the Indonesian Balance of Payment.